Cosmopolitanism, Translocality, Astronoetics: A Multi-Local Vantage Point - Vargas-Cetina, Gabriela; Kang, Manpreet Kaur (Review of International American Studies, 2020)
The world in which we live is crisscrossed by multiple flows of people, information, non-human life, travel circuits and goods. At least since the Sixteenth Century, the Americas have received and generated new social, cultural and product trends. As we see through the case studies presented here, modern literature and dance, the industrialization of food and the race to space cannot be historicized without considering the role the Americas, and particularly the United States, have played in all of them. We also see, at the same time, how these flows of thought, art, science and products emerged from sources outside the Americas to then take root in and beyond the United States. The authors in this special volume are devising conceptual tools to analyze this multiplicity across continents and also at the level of particular nations and localities. Concepts such as cosmopolitanism, translocality and astronoetics are brought to shed light on these complex crossings, giving us new ways to look at the intricacy of these distance-crossing flows. India, perhaps surprisingly, emerges as an important cultural interlocutor, beginning with the idealized, imagined versions of Indian spirituality that fueled the romanticism of the New England Transcendentalists, to the importance of Indian dance pioneers in the world stage during the first part of the twentieth century and the current importance of India as a player in the race to space.